Relationship Between Parents' Educational Level and Family Emotional Support on Students' Interest in Learning Inpres 01 Paniki Bawah Elementary School - Meisara Leonita Horman; Roeth A. O Najoan; Richard D.H. Pangkey (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This study aims to determine the relationship between parental education level and family emotional support on students' learning interest at SD Inpres 01 Paniki Tengah. Interest in learning is one of the important factors that affect the success of students in the learning process. The family environment, particularly the level of parental education and the emotional support provided to the child, is thought to play a significant role in shaping students' interest in learning. This study uses a quantitative approach with a correlational method. The population in this study consists of all students at SD Inpres 01 Paniki Tengah, with sampling techniques selected according to the research needs. Data collection is carried out through questionnaires and documentation. The data obtained is then analyzed using statistical correlation analysis to determine the relationship between the research variables. The results of the study are expected to provide an overview of the relationship between parents' education level, family emotional support, and students' learning interest. The findings are expected to be considered by schools, teachers, and parents in enhancing students' interest in learning through optimal family support.